GC–MS profiling, descriptive sensory analysis, and consumer acceptance of Costa Rican papaya (Carica papaya L.) fruit purees. (15th May 2018) - Lieb, Veronika M.; Esquivel, Patricia; Cubero Castillo, Elba; Carle, Reinhold; Steingass, Christof B.
Graphical abstract: Highlights: A total of 83 volatiles was detected in Costa Rican papaya purees. Classification of purees using multivariate statistics (PCA, PLS-DA). Identification of substantial markers for class separation. Pleasant odour attributes characterized terpene- and lactone-rich cultivars. Consumer acceptance of papaya purees differed. Abstract: Volatiles of papaya purees from four Costa Rican cultivars were analysed by solid-phase microextraction and gas chromatography-mass spectrometry. A total of 83 volatiles was assigned in the purees, of which 19 were detected for the first time as papaya constituents. As revealed by multivariate statistics, i.e., principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA), the purees may be allocated to terpene- and lactone-rich ('SH-5'), ester-containing ('Criolla'), and intermediate chemotypes ('Pococí' and 'Silvestre'). Descriptive sensory analysis and a consumer acceptance test were additionally performed. Floral, fruity, and honey-like notes were perceived at significantly higher intensities in 'SH-5' puree. The latter descriptors strongly correlated with volatiles discriminating 'SH-5' in the PCA and PLS-DA, respectively. Consumer acceptance of the papaya purees differed significantly. 'Pococí' and 'SH-5' purees appear to be suitable for improving the nutritional value of blended fruit juices without impairing their sensory quality.